Uncovering the Impact of Organizational Communication Climate on Communication Satisfaction: A Systematic Review of the Principles of Communication in Islam - Rijal Fadilah; Rismi Juliadi; Nuria Astagini (Sahafa Journal of Islamic Communication, 2024)
In an increasingly dynamic context, organizational communication climate is an important aspect that affects employee performance and job satisfaction. This research systematically analyses the existing literature to understand how organizational communication climate affects employee communication satisfaction. Using the Systematic Literature Review method, this study identifies, assesses, and synthesizes research results from 2010 to 2021 to build a more robust understanding of the relationship between communication climate and communication satisfaction in various forms of organizations. As part of the review process, relevant articles were identified by searching major academic databases using appropriate keywords. After the selection process, seven studies were selected based on the established inclusion and exclusion criteria. The analysis showed that a positive communication climate significantly increases employee communication satisfaction. The findings indicate a significant relationship between effective communication practices and employee satisfaction levels, where two-way communication, transparency and inclusiveness play an important role. This research has significant implications for organizational stakeholders in developing effective communication strategies to improve employee satisfaction and performance. Recommendations for future research are also presented, including further exploring mediating factors that may influence the relationship between communication climate and satisfaction. By understanding these dynamics, organizations can design a more supportive and communicative work environment for their employees. Keywords : Efectivity; Communication Climate; Communication Satisfaction; Organization; Systematic Literature Review